Potensi Senyawa Bioaktif dari Bajakah Spatholobus littoralis Hassk. Sebagai Antikanker terhadap Sel MCF-7 secara In Vitro - Habibi, Alif Rahman; Arfan, Alya Rahmaditya; Anwar, Khoirul; Azizah, Anggia; Fathia, Mona; Winanda, Witri; Berlyansyah, Azizul (Jurnal Ilmu Alam dan Lingkungan, 2025)
Bajakah (Spatholobus littoralis Hassk.) is a plant from the Angiospermae group, belonging to the Leguminosae family, that grows in Kalimantan. This plant contains secondary metabolites with potential anticancer activity. Cancer is characterized by uncontrolled cell proliferation beyond normal mechanisms, leading to abnormal tissue growth and invasion. It is one of the leading causes of death worldwide, including breast cancer. In 2022, approximately 2.3 million women were diagnosed with breast cancer, with 670,000 deaths recorded globally, while around 1.63 million women were still living with the disease by the end of the year. This study aimed to evaluate the anticancer activity of Bajakah Spatholobus littoralis Hassk. against MCF-7 breast cancer cells using the MTS assay. The results showed that Bajakah extract exhibited low toxicity toward the MCF-7 cell line, with an IC50 value of 1,098.77 ppm. Therefore, it can be concluded that Bajakah Spatholobus littoralis Hassk., tested with the MTS method, is not cytotoxic to breast cancer cells. Further studies are recommended to investigate its potential effects on other cancer cell types